Investigating Local Resources and Wisdom in Partner Regions Surrounding the Nation's Capital for Road Network Development - Junaidi .; Sakti A. Adisasmita; Muhammad S. Pallu; M. Isran Ramli (Civil Engineering Journal, 2022)
The development of the New Indonesia’s Capital, called the IKN, will undoubtedly draw many people to come and engage in the IKN region, although not inside the IKN area, since the development is confined to a small area with smart city, blue city, and forest city ideas merged. Restrictions on mobility inside the IKN area will almost definitely create issues for road network connectivity across IKN's surrounding areas, so it was deemed essential to have a road network development model that maintains IKN as a limited area while also functioning as a catalyst for economic growth in partner areas. The focus of this research is to provide a model for developing a road network based on local wisdom and the resources of each partner region surrounding IKN. The method employed in this study is based on gathering secondary data of the surrounding areas, which has local resources and local wisdom. The resources and the local wisdom are considered a trip attractor. The IKN masterplan data was also employed in this study as the main subject. Principles and road network development theory were used to analyze the data. The findings of this research led to the development of a new road network in various regions, including Senoni, Gusig, and Tukuq. This road network is deemed necessary to be developed, due to its trip attraction potential. It is hoped that the implementation of these new road networks will also have positive impacts on the development of partner areas surrounding IKN. Doi: 10.28991/CEJ-2022-08-05-06 Full Text: PDF